USM BANKING ON IDEAS IN DEALING WITH 2016 CHALLENGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 18 January 2015 – The introduction of an Idea Bank as a platform for the Universiti Sains Malaysia (USM) community to generate constructive ideas for the development of the university is hoped to become a medium which could assist the university to face the challenges in 2016.